GgClusterNet: An R package for microbiome network analysis and modularity‐based multiple network layouts. Issue 3 (13th June 2022) - Wen, Tao; Xie, Penghao; Yang, Shengdie; Niu, Guoqing; Liu, Xiaoyu; Ding, Zhexu; Xue, Chao; Liu, Yong‐Xin; Shen, Qirong; Yuan, Jun
Abstract: The network analysis has attracted increasing attention and interest from ecological academics, thus it is of great necessity to develop more convenient and powerful tools. For that reason, we have developed an R package, named "ggClusterNet, " to complete and display the network analysis in an easier manner. In that package, ten network layout algorithms are designed to better display the modules of microbiome network (randomClusterG, PolygonClusterG, PolygonRrClusterG, ArtifCluster, randSNEClusterG, PolygonModsquareG, PolyRdmNotdCirG, model_Gephi.2, model_igraph, and model_maptree). For the convenience of the users, many functions related to microbial network analysis, such as corMicor(), net_properties(), node_properties(), ZiPiPlot(), random_Net_compate(), are integrated to complete the network mining. Furthermore, the pipeline function named network.2() and corBionetwork() are also added for the quick achievement of the network or bipartite network analysis as well as their in‐depth mining. The ggClusterNet is publicly available via GitHub (https://github.com/taowenmicro/ggClusterNet/ ) or Gitee (https://gitee.com/wentaomicro/ggClusterNet ) for users' access. A complete description of the usages can be found on the manuscript's GitHub page (https://github.com/taowenmicro/ggClusterNet/wiki ). Highlights: ggClusterNet is an R package for microbial networks. Analysis functions could help the user to easily complete network analysis and interpretation. Ten network layout algorithms allow users more alternatives to plot the network and generate published‐ready figures. It is free to access on GitHub and Gitee. Abstract : ggClusterNet is an R package for microbial networks analysis and interpretation. Ten network layout algorithms  allow users more alternatives to plot the network and generate published‐ready figures. It is free to access on GitHub and Gitee.